TINGKAT HUBUNGAN KOORDINASI MATA-KAKI DAN DAYA LEDAK OTOT TUNGKAI DENGAN KEMAMPUAN PASSING LAMBUNG TIM SSB R2 SOLO - Wisnu Cahyo Dewo Wisnu; Agam Akhmad Syaukani (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2023)
This study aims to find the relationship between eye-foot coordination and leg muscle explosive power with the gastric Passing ability of the SSB R2 Solo team. This research is of a quantitative type with a correlation method because it seeks a relationship between the Passing abilities of football players. The number of subjects in this study were 14 people, the researcher used correlation and the data in this study were taken by eye-foot coordination tests, leg muscle explosive power tests and stomach Passing ability tests as data collection instruments. The results of this study showed that there was no significant relationship (p>0.05) between ankle-foot coordination and gastric Passing ability, there was no significant relationship (p>0.05) between leg muscle explosive power and gastric Passing ability and there was no significant relationship (p>0.05) between eye-foot coordination and leg muscle explosive power on gastric Passing ability